Feasibility and outcome of reproducible clinical interpretation of high-dimensional molecular data: a comparison of two molecular tumor boards - Rieke, Damian; de Bortoli, Till; Horak, Peter; Lamping, Mario; Benary, Manuela; Jelas, Ivan; Rüter, Gina; Berger, Johannes; Zettwitz, Marit; Kagelmann, Niklas; Kind, Andreas; Fabian, Falk; et al. (BMC medicine, 2022)
Structured and harmonized implementation of molecular tumor boards (MTB) for the clinical interpretation of molecular data presents a current challenge for precision oncology. Heterogeneity in the interpretation of molecular data was shown for patients even with a limited number of molecular alterations. Integration of high-dimensional molecular data, including RNA- (RNA-Seq) and whole-exome sequencing (WES), is expected to further complicate clinical application. To analyze challenges for MTB harmonization based on complex molecular datasets, we retrospectively compared clinical interpretation of WES and RNA-Seq data by two independent molecular tumor boards.